2019
DOI: 10.1108/ir-11-2018-0230
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of stimuli-current thresholds on the non-steady contact condition

Abstract: Purpose This paper aims to investigate the perception threshold (PT) of electrotactile stimulation under non-steady contact condition (NSCC) which is rarely considered in previous reports mainly because of the difficulty with experimental control. Three factors of NSCC are involved, including the current alternating frequency, the tapping interval of stimulation and the stimulating area of skin. The study is aimed at providing the basic PT data for design and application of wearable and portable electrotactile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In the previous study, we challenged the NSCC perception threshold investigation with psychophysical method (Chen et al , 2019) and found that the perception threshold of NSCC was much less than that of steady contact condition, SCC. As we know, psychophysical method is based on the protocol of question and answer, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In the previous study, we challenged the NSCC perception threshold investigation with psychophysical method (Chen et al , 2019) and found that the perception threshold of NSCC was much less than that of steady contact condition, SCC. As we know, psychophysical method is based on the protocol of question and answer, i.e.…”
Section: Introductionmentioning
confidence: 99%